Botulinum Toxin Treatment for Mild to Moderate Platysma Bands: A Systematic Review of Efficacy, Safety, and Injection Technique. (25th July 2018) - Sugrue, Conor M; Kelly, Jack L; McInerney, Niall
Abstract: Background: Platysma bands are characteristic of an aging neck. Resection and plication of the platysma muscle is the basis of treatment. However, unfavorable surgical outcomes and improved understanding of platysma band etiology have shifted treatment towards nonsurgical rejuvenation. Objectives: The aim of this paper was to assess the efficacy, injection techniques, and complications associated with botulinum toxin injection for the treatment of platysma bands. Methods: A systematic literature search was performed to identify articles reporting botulinum toxin injections for platysma bands in neck rejuvenation. The search included published articles in three electronic databases—Ovid MEDLINE, EMBASE, and the Cochrane Library—between January 1985 and December 2017. Results: Three studies met the inclusion criteria, with a total of 78 patients undergoing botulinum toxin injection for platysma bands. Incobotulinumtoxin A was used in 62.3% ( n = 45/78) of patients, with 38.4% ( n = 30/78) receiving abobotulinumtoxin A. Efficacy was assessed using the Merz platysma score scale. A mean score improvement of 2.0 points, with a response rate of 93.7%, was observed after 14 ± 2 days. At 3 months, the mean score improvement was 1.2 points with a response rate of 86%. Patient-reported metrics demonstrated an improvement in 91% ( n = 71/78) of subjects. The three studies used a standard injection technique, with a maximum 20 IU of incobotulinumtoxin A and 5 U abobotulinumtoxin A administered per band. Complications were reported in 15.4% ( n = 12/78) of patients, with none requiring further intervention. Conclusions: Botulinum toxin is a highly effective treatment for isolated platysma bands. A safe injection technique is described and recommended for clinical practice. Level of Evidence: 4: